2005
DOI: 10.21273/horttech.15.2.0399
|View full text |Cite
|
Sign up to set email alerts
|

Single-centered and Super Colossal Bulbs from Yellow Onion Cultivars

Abstract: Onion (Allium cepa) cultivars for commercial production in eastern Oregon and southwestern Idaho are evaluated annually in replicated yield trials conducted at the Malheur Experiment Station, Oregon State University, Ontario. Market demand has progressively called for larger bulb size and bulbs with single centers. At harvest onions were evaluated for maturity, number of bolters, and single centeredness. Cultivars showed a wide range of bulbs with only one growing point or “b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Redwing, which is another Bejo Seeds cultivar, was the only red cultivar with a higher than average firmness rating (3.6) ( Table 7). Single centeredness is known to be a heritable trait in onion (Cramer, 2006;Shock et al, 2005;Wall et al, 1996), so it is not surprising that the ANOVA for this study reported a significant cultivar effect for the percentage of functionally single-centered onions in these trials (Tables 6 and 7). The percentage of bulbs with functional single centers was 57.8% when averaged across years and cultivars (Table 7).…”
Section: Variety Trialsmentioning
confidence: 62%
See 3 more Smart Citations
“…Redwing, which is another Bejo Seeds cultivar, was the only red cultivar with a higher than average firmness rating (3.6) ( Table 7). Single centeredness is known to be a heritable trait in onion (Cramer, 2006;Shock et al, 2005;Wall et al, 1996), so it is not surprising that the ANOVA for this study reported a significant cultivar effect for the percentage of functionally single-centered onions in these trials (Tables 6 and 7). The percentage of bulbs with functional single centers was 57.8% when averaged across years and cultivars (Table 7).…”
Section: Variety Trialsmentioning
confidence: 62%
“…Each onion was cut in half (longitudinally) and the number of sprouted bulbs was recorded, and then cut again (latitudinally) to determine the number of bulbs with single centers or small multiple centers not exceeding 1 inch in diameter. Onion bulbs with single centers or small multiple centers are said to be ''functionally'' single centered (Shock et al, 2005). The numbers of bulbs with bacterial bulb rot and fungal neck rot were also recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cepae) diseases (Shock et al, 2000). Starting in 2000, two additional variety characteristics were evaluated: super colossal size bulbs (>4¼ inches diameter) and single-centered bulbs (Shock et al, 2005a).…”
mentioning
confidence: 99%